Indirect method estimates of correlation function - Денисюк, В.П.; Світлична, А.А. (Proceedings of National Aviation University (archive), 2005)
The connection between estimates of correlation function constructed by direct and indirect methods is considered in this paper that had enabled to find out a nature of properties of these estimates.